Evaluation of the Volume Stability and Resource Benefit of Basic Oxygen Furnace Slag and Its Asphalt Mixture Based on Field Application - Yuechao Zhao; Jiangkai Song; Jun Xie; Fusong Wang; Meizhu Chen; Shaopeng Wu (Advances in Civil Engineering)
Applying basic oxygen furnace (BOF) slag as aggregate in asphalt mixture is continuously investigated due to the increasing shortage of natural aggregate in recent years. However, the negative effect of BOF’s expansion in water greatly limits its further application in pavement construction. To address this problem, this paper studied the volume stability of BOF, and its asphalt mixture relied on actual engineering. The asphalt mixtures contained BOF aggregate was designed by the Marshall method with three different gradation types (AC-16, AC-20, and ATB-25). Besides, both laboratory samples and the core samples from field drilling were investigated in volume expansion rate after curing in a water bath. The economic and resource benefits of BOF replacement of natural aggregates were also analyzed. The results showed that the free calcium oxide content of BOF slag is positively related to the particle sizes. Nevertheless, the expansion rates of both the BOF aggregate and its asphalt mixture were less than 1%, which meant the BOF aggregate applied to the asphalt mixture meets the practical engineering requirements. The maximum allowable free calcium oxide content for large-grain size of steel slag is the smallest; it is also recommended that the expansibility of large-grain steel slag should be the first concern in the application. The resource assessment indicated that the use of steel slag for the construction of a trial section of one kilometer of single lane can save 967 tons of natural aggregates. The economic evaluation showed that the use of steel slag instead of natural aggregates for surface course construction could reduce the investment by 16.87%. The experimental methods and conclusions mentioned in this article provide stable references to enhance the development of sustainable pavement by recycling metallurgical slag in highway construction.